Noncovalent Spin‐Labeling of DNA and RNA Triplexes. Issue 2 (21st January 2020) - Kamble, Nilesh; Wolfrum, Manpreet; Halbritter, Thomas; Sigurdsson, Snorri T.; Richert, Clemens
Abstract: Studying nucleic acids often requires labeling. Many labeling approaches require covalent bonds between the nucleic acid and the label, which complicates experimental procedures. Noncovalent labeling avoids the need for highly specific reagents and reaction conditions, and the effort of purifying bioconjugates. Among the least invasive techniques for studying biomacromolecules are NMR and EPR. Here, we report noncovalent labeling of DNA and RNA triplexes with spin labels that are nucleobase derivatives. Spectroscopic signals indicating strong binding were detected in EPR experiments in the cold, and filtration assays showed micromolar dissociation constants for complexes between a guanine‐derived label and triplex motifs containing a single‐nucleotide gap in the oligopurine strand. The advantages and challenges of noncovalent labeling via this approach that complements techniques relying on covalent links are discussed. Abstract :